The Effect of Post-Covid-19 Cultural Arts Learning on Behavior, Especially the Study Habits of Students in Class XII MIPA 1 SMA Negeri 04 Kepahiang - Shella Triandani; Tulus Handra Kadir (Universitas Negeri Padang, 2023)
This study aims to determine and describe the effects of learning arts and culture post-COVID-19 on behavior, especially study habits, in Class XII MIPA 1 SMA Negeri 4 Kepahiang. This type of research is qualitative research with descriptive methods. The research instrument was the researcher herself, assisted by supporting instruments such as writing instruments, observation notes, and cellphone cameras. Data collection techniques carried out by way of literature study, observation, interviews, and documentation the steps for analyzing data are classifying data, clarifying problems, analyzing data, describing data, and concluding data. The results of the study stated that the results of post-covid observations of cultural arts learning had shown a lot of progress, especially in their study habits. By implementing face-to-face learning, it can be said that it has quite an effect on class XII MIPA 1 students. This effect is due to the direct supervision of the teacher within the scope of the school. When learning returns to offline, where students are able to follow the learning process coherently, get good supervision from the teacher, and are more creative in expressing their imagination, As well as direct communication between teachers and students, this helps students better understand the learning material provided by the teacher, and of course, their study habits become regular and vice versa. If learning is not supervised by the teacher, students will be lazy.